Marketing Issues of the eighties - Hazel T. Suchard (South African Journal of Business Management, 1983)
Important aspects of marketing in the Eighties are identified and analysed. Economic factors, consumerism and consumer movements as well as legislation, demographic changes, technological developments, international events, and international competition and the influence of all these factors upon marketing strategy is discussed. Finally, changes in important components of a future marketing strategy are presented.
Keywords: 650